Homogenitas, Stabilitas, dan Konfirmasi Molekuler Biakan Kering Beku Campuran Escherichia coli dan Salmonella Typhimurium - Nurjanah, Siti; Agesti, Puja; Rahayu, Winiati Pudji; Hasanah, Uswatun; Nanda, Riska Dwi (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Food product testing laboratories play a prominent role in ensuring safety and quality of products manufactured by food industries; therefore, they shall comply with standards of ISO/IEC 17025:2017. Although a proficiency test for microbiological parameter is required to evaluate testing laboratories' performance in considering food product quality and safety, the existence of proficiency test organizations in Indonesia is currently still limited. This study was conducted to determine the appropriate types of cryoprotectant, evaluate the degree of homogeneity and stability of the freeze-dried cultures of Escherichia coli and Salmonella Typhimurium for preparation of proficiency testing item, as well as molecular confirmation of E. coli and S. Typhimurium bacteria using PCR. The freeze-dried cultures were prepared for the purpose of producing the proficiency testing object. Three main stages were conducted, namely cryoprotectant effectiveness test, homogenization test and stability test at 4 °C storage temperature for four different times (0, 7, 14, 65 days), as well as molecular confirmation test. The best cryoprotectant treatment was using 10% trehalose with the viabie E. coli and S. Typhimurium respectively 5.58±0.25 and 5.31±0.09 log CFU/mL. Freeze-dried culture samples of E. coli and S. Typhimurium was declared homogeneous and stable based on ISO 13528:2015 calculations. E. coli bacteria were confirmed using standard PCR with 16S rRNA primer, while S. Typhimurium was confirmed using rt-PCR with invA primer.